Conscious Self-Regulation and Academic Motivation as Resources for Students to Perform Research Project Work - V.I. Morosanova; E.V. Filippova; T.G. Fomina (Moscow State University of Psychology and Education, 2023)
The article presents the results of an empirical study of the relationship between the regulatory competencies of students, different types of academic motivation and successful performance of the research project work. Diagnostics of regulatory competencies was carried out by means of Morosanova’s "Self-regulation profile of learning activities questionnaire - SRPLAQ-M"; academic motivation was assessed using Gordeeva’s "Scales of academic motivation of schoolchildren". The diagnostics was carried out at the beginning of the academic year. Criteria-based assessments, set by the expert teachers, were used as indicators of the project work success. The study, performed on a sample of 9th grade students (N=187, 15-16 years old), provided evidence that regulatory competencies and motivation serve as prerequisites for the students’ success in research project work. The study allowed to empirically distinguish between the universal and special regulatory competencies. The data analysis revealed the resource role of regulatory competencies in performing an individual research project. It is shown that the general level of the conscious self-regulation development characterizes the universal resources for successful performance of an individual project and is positively associated with all expert criteria for assessment research project success. Special regulatory resources are the modeling of significant conditions and evaluating the results of actions. The study also revealed a mediator role of the regulatory competence of evaluating results in the relationship between the students’ academic motivation and the final assessment of the research project.